2011
DOI: 10.1152/ajpcell.00438.2010
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical properties of normal and diseased renal glomeruli

Abstract: The mechanical properties of tissues and cells including renal glomeruli are important determinants of their differentiated state, function, and responses to injury but are not well characterized or understood. Understanding glomerular mechanics is important for understanding renal diseases attributable to abnormal expression or assembly of structural proteins and abnormal hemodynamics. We use atomic force microscopy (AFM) and a new technique, capillary micromechanics, to measure the elastic properties of rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 44 publications
(78 reference statements)
4
86
0
1
Order By: Relevance
“…This distribution corresponds to the domains of highest cholesterol content in podocytes on the basis of earlier freeze-fracture studies (43). The glomerular capillary is a relatively high-pressure microvascular bed, and its walls are unusually rigid (4,70). For this reason, podocyte foot processes will be exposed to continuous highfrequency mechanical stimuli originating from the cardiac cycle, as well as slower fluctuations associated with myogenic autoregulatory responses and tubuloglomerular feedback (19).…”
Section: Discussionmentioning
confidence: 87%
“…This distribution corresponds to the domains of highest cholesterol content in podocytes on the basis of earlier freeze-fracture studies (43). The glomerular capillary is a relatively high-pressure microvascular bed, and its walls are unusually rigid (4,70). For this reason, podocyte foot processes will be exposed to continuous highfrequency mechanical stimuli originating from the cardiac cycle, as well as slower fluctuations associated with myogenic autoregulatory responses and tubuloglomerular feedback (19).…”
Section: Discussionmentioning
confidence: 87%
“…For example, it was shown that conditionally immortalized glomerular podocytes from a mouse model of HIVassociated nephropathy (HIVAN) are substantially softer than normal podocytes (by 25%), as assessed by atomic force microscopy (AFM) and microaspiration (Tandon et al, 2006). At a stage of the disease that showed no detectable pathological changes, the glomeruli from these mice were 30% softer than normal glomeruli (1.5 kPa compared with 2.5 kPa, as measured by AFM) (Wyss et al, 2011). Glomeruli and podocytes in other disease models are also significantly softer than normal cells, indicating that the increased mechanical deformability of podocytes and glomeruli might be a common feature of a number of renal diseases.…”
Section: Renal Glomerular Diseasementioning
confidence: 99%
“…Because the moduli of reconstituted actin networks are highly sensitive to cross-linker affinity and concentration (1,2,19), we hypothesized that changes in actin cross-linking will also significantly impact the total force and work exerted by an active cell on its environment. However, the effect of this mutation, or variable cross-linking in general, on the dynamics and forces of cells is largely unknown (20). Understanding how cross-linker binder affinity changes force generation will provide essential insight into how cells modulate their mechanics, and exert forces on their surrounding environment.…”
mentioning
confidence: 99%